Reconstructing oceanographic conditions through the deglacial and holocene (ca. 15 ka) at the sub-antarctic island of South Georgia - Dejardin, Rowan L.S. (2018)
South Georgia is located in the path of the Antarctic Circumpolar Current (ACC) and the Southern Hemisphere Westerly Winds (SWW), south of the Antarctic Polar Front (APF) and surrounded by an anticyclonic loop of the Southern ACC Front (SACCF). The waters surrounding South Georgia are highly productive and variability in the interaction of the SACCF with the island may impact productivity on the shelf. Of wider significance is the large phytoplankton bloom that occurs to the north-west of South Georgia, where the SACCF retroflects to return to its cyclonic circumpolar circulation. This bloom represents one of the largest seasonal sinks of atmospheric CO2 in the Southern Ocean. Given the likely importance of the Southern Ocean as a carbon sink/source during the transition between glacial and interglacial periods a better understanding of the bloom dynamics could be important to our assessment of the Southern Ocean’s role in these transitions. This thesis investigates deglacial and Holocene variability in productivity and sea-surface temperature on the north-eastern shelf of South Georgia, through the development of the first palaeoceanographic records from the island. To support the palaeoceanographic interpretation a comprehensive taxonomic study of the benthic foraminifera of the South Georgia shelf was developed, and the importance of foraminiferal ecology to test carbon isotope composition was investigated. The taxonomic assessment of the shelf benthic foraminifera resulted in the description of 78 species, assigned to 57 genera from 34 families (of these 58 species are identified to species level, while 20 species are discussed in open nomenclature). The investigation of foraminiferal ecology highlighted the importance of understanding the ecology of the species being utilised for isotope analysis to the application of this data to palaeoceanographic interpretations. In addition, a novel calcification strategy was proposed, in which a most benthic foraminiferal calcification occurs at the sediment-seawater interface. The palaeoceanographic records presented here support the hypothesis that the ice sheet on South Georgia during the Last Glacial Maximum extended onto the shelf. Potential evidence for the formation of a calving bay re-entrant over Royal Bay trough indicates that grounded ice may have been present on the shallower shelf until ca. 15 cal. kyr BP, having retreated rapidly over the deeper cross shelf troughs after the Last Glacial Maximum. Evidence is also found for the influence of the Antarctic Cold Reversal at South Georgia. During the Holocene, I propose that both sea-surface temperature (SST) and shelf productivity may have been driven by variation in the SWW, except during the early Holocene when sea-ice proximity may play an important role in productivity variability. Changes in the intensity of the SWW at South Georgia drive SST through their impact of local foehn wind frequency and shelf productivity through variation in coastal upwelling. This interpretation of the variability in shelf SST and productivity indicates that the SWW were more intense at South Georgia during the mid-Holocene, and weaker during the early and late Holocene. Similar patterns of SWW variability have been reported from other locations at the same latitude, although some records have been interpreted to reveal different patterns of SWW change. Variation in SWW intensity at South Georgia may be due to either latitudinal migration of the SWW, or to expansion and contraction of the core SWW band, both of which are linked to Southern Hemisphere temperature change.